2018
DOI: 10.1111/bph.14174
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxynonenal‐induced GPR109A (HCA2 receptor) activation elicits bipolar responses, Gαi‐mediated anti‐inflammatory effects and Gβγ‐mediated cell death

Abstract: These results revealed that 4-HNE is a strong agonist for GPR109A that induces G -dependent anti-inflammatory and G -dependent cell death responses. Moreover, the findings indicate that specific intracellular signalling molecules, but not GPR109A, can serve as therapeutic targets to block 4-HNE-induced cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Since the identification of GPR109A, a Gi/o‐coupled receptor, as the molecular target for niacin (20, 22, 36), most studies have focused on its pronounced hypolipidemic and cardioprotective action. Recent investigations have also shed light on the anti‐inflammatory and anti‐oxidative effects of GPR109A (22, 3740). However, little attention has been paid to the potential of this receptor to favorably modulate de novo lipogenesis and energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the identification of GPR109A, a Gi/o‐coupled receptor, as the molecular target for niacin (20, 22, 36), most studies have focused on its pronounced hypolipidemic and cardioprotective action. Recent investigations have also shed light on the anti‐inflammatory and anti‐oxidative effects of GPR109A (22, 3740). However, little attention has been paid to the potential of this receptor to favorably modulate de novo lipogenesis and energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Since in response to hydroxynonenal GPR109A was demonstrated to induce excessive Ca 2+ mobilization and the subsequent cell death in the retinal pigmented and colon epithelial cells [47], we speculated that the same may occur in β-cells where GPR109A is expressed.…”
Section: Discussionmentioning
confidence: 97%
“…These authors found that RPN supplementation may amplify the systemic inflammation-like condition in early lactation, and they suggested the markedly high-dosage RPN might be related to the indications of inflammation-like condition. To support this hypothesis, Gautam et al (77) found low concentration of niacin down-regulated the pro-inflammatory cytokines, but the high concentration of niacin induced cell apoptosis.…”
Section: Niacin Supplementation During Heat Stressmentioning
confidence: 98%
“…Recent studies demonstrated that nicotinic acid has a profound anti-inflammatory effect by an HCA 2 -dependent mechanism in mouse alveolar macrophages (75) , colonic macrophages, dendritic cells (76) , human retinal pigmented epithelial cells, kidney cells (77) , etc. This raises the question of whether nicotinic acid exerts a similar anti-inflammatory effect in ruminants.…”
Section: Niacin Supplementation During Heat Stressmentioning
confidence: 99%